O bairro Zumbi na perspectiva de território negro e lugar de práticas culturais afro-brasileiras em Cachoeiro de Itapemirim, Espírito Santo - Dias, Silvia de Souza (2014)
The research proposes an interpretation of Zumbi neighborhood, the most populous Itapemirim - ES, from a perspective of black territory and place of african-Brazilian cultural practices. Place of diversity, the neighborhood has religious and cultural manifestations african-Brazilian, among them Samba, Caxambu and Umbanda. The research used the methodology of social history and historical anthropology from a historical approach, political and economic of the Holy Spirit, in which we observed the rituals and symbols, emphasizing the narrative of social actors.